PERSPECTIVES OF FUNCTIONING THE TECHNOLOGICAL PLATFORM IN THE CONDITIONS OF NEW INDUSTRIAL REVOLUTION IN UKRAINE - Galiuk, I.B. (The actual problems of regional economy development, 2018)
The article is aimed at studying the functioning and development of technological platforms as progressive centers of innovation activity on the basis of integrated strategies of scientific and technical directions, which allow obtaining significant social and economic effect. In the conditions of a new industrial revolution, this issue becomes of special significance. Based on the analysis of foreign experience of the operation of technology platforms and statistical data on research and innovation activities in Ukraine, it has been determined that to date, the main preconditions for the implementation of the plans are not provided. These questions can be solved only on the basis of the analysis of the triad "science - business - power" as a mutually determining component of breakthrough performance.